Handbook of Religion and Spirituality in Social Work Practice and Research - Loue, Sana (Springer New York : Imprint: Springer, 2017)
This singular reference explores religion and spirituality as a vital, though often misconstrued, lens for building better understanding of and empathy with clients. A diverse palette of faiths and traditions is compared and contrasted (occasionally with secularism), focusing on areas of belief that may inspire, comfort, or trouble clients, including health and illness, mental illness, healing, coping, forgiveness, family, inclusion, and death. From assessment and intervention planning to conducting research, these chapters guide professionals in supporting and assisting clients without minimizing or overstating their beliefs. In addition, the book's progression of ideas takes readers beyond the well-known concept of cultural competence to model a larger and more meaningful cultural safety. Among the topics included in the Handbook: Integrating religion and spirituality into social work practice. Cultural humility, cultural safety, and beyond: new understandings and implications for social work. Healing traditions, religion/spirituality, and health. Diagnosis: religious/spiritual experience or mental illness? Understandings of dying, death, and mourning. (Re)building bridges in and with family and community. Ethical issues in conducting research on religion and spirituality. The Handbook of Religion and Spirituality in Social Work Practice and Research is a richly-textured resource for social workers and mental health professionals engaged in clinical practice and/or research seeking to gain varied perspectives on how the religion and spirituality of their clients/research participants may inform their work.